The wound‐healing effects of a next‐generation anti‐biofilm silver Hydrofiber wound dressing on deep partial‐thickness wounds using a porcine model. Issue 5 (11th June 2018) - Davis, Stephen C.; Li, Jie; Gil, Joel; Valdes, Jose; Solis, Michael; Higa, Alex; Bowler, Philip
Abstract : Topical antimicrobials are widely used to control wound bioburden and facilitate wound healing; however, the fine balance between antimicrobial efficacy and non‐toxicity must be achieved. This study evaluated whether an anti‐biofilm silver‐containing wound dressing interfered with the normal healing process in non‐contaminated deep partial thickness wounds. In an in‐vivo porcine wound model using 2 pigs, 96 wounds were randomly assigned to 1 of 3 dressing groups: anti‐biofilm silver Hydrofiber dressing (test), silver Hydrofiber dressing (control), or polyurethane film dressing (control). Wounds were investigated for 8 days, and wound biopsies ( n = 4) were taken from each dressing group, per animal, on days 2, 4, 6, and 8 after wounding and evaluated using light microscopy. No statistically significant differences were observed in the rate of reepithelialisation, white blood cell infiltration, angiogenesis, or granulation tissue formation following application of the anti‐biofilm silver Hydrofiber dressing versus the 2 control dressings. Overall, epithelial thickness was similar between groups. Some differences in infiltration of specific cell types were observed between groups. There were no signs of tissue necrosis, fibrosis, or fatty infiltration in any group. An anti‐biofilm silver Hydrofiber wound dressing did not cause any notable interference with normal healing processes.